The guidance services in Pasay City high schools as perceived by students, teachers, administrators and guidance counselors - Sayo, Teresita P. (Capili) 1932-
This study measured the extent of the procedural implementation of the guidance services recommended by the Bureau of Public Schools as perceived by senior students, homeroom advisers, administrators and counselors.